A metal oxide affinity probe derived from MIL-125 for selective enrichment of endogenous phosphopeptides. Issue 7 (18th February 2021) - Zhao, Yameng; Zhang, Lingyi; Cao, Licheng; Zhang, Lei; Zhang, Weibing
Abstract : Highly effective enrichment of endogenous phosphopeptides from complex biological samples is an essential and crucial theme in the analysis of phosphopeptidomics. Abstract : Highly effective enrichment of endogenous phosphopeptides from complex biological samples is an essential and crucial theme in the analysis of phosphopeptidomics. Herein, an ordered mesoporous TiO2 /C composite (denoted as Ti–MCM) was prepared by the pyrolysis of MIL-125 under a N2 atmosphere. The obtained Ti–MCM possesses a high specific surface area (165 m 2 g −1 ), a uniform pore size (3.75 nm), and a large amount of Ti (46%). By utilizing the selective chelation between Ti–MCM and phosphopeptides, 25 phosphopeptides were detected in α-casein digest after enrichment. The material shows good selectivity even in the presence of 2000-fold excess of interference peptides. It was also used to enrich endogenous phosphopeptides from the complex samples of human serum and saliva and showed a good performance.